Comparison of the Efficacy of Fluorometholone With and Without Benzalkonium Chloride in Ocular Surface Disease. Issue 2 (February 2016) - Kim, Yeoun-Hee; Jung, Jae-Chang; Jung, Soon-Young; Yu, Sung; Lee, Kyoo Won; Park, Young Jeung
Abstract : Purpose: The purpose of this study was to compare the cytotoxicity and antiinflammatory effect of preserved and unpreserved 0.1% fluorometholone (FML). Methods: Drug-induced morphological changes and cytotoxicity were examined in human corneal epithelial cells. Dry eye was induced in mice by treatment with 0.2% benzalkonium chloride (BAC) for the first 2 weeks, and then, the eyes (4 groups; Normal saline, BAC, preserved FML, and unpreserved FML) were treated thrice daily with each formulation for the next 2 weeks. Corneal tissues were embedded in paraffin and stained with hematoxylin and eosin for histopathological examination. Immunofluorescence staining was performed for tumor necrosis factor-α, interleukin-6, and human leukocyte antigen–DR. Terminal deoxynucleotidyl transferase dUTP nick end labeling assay was performed to evaluate drug-induced cytotoxicity. Results: BAC and preserved FML caused cell shrinkage and detachment from the plate in a dose-dependent manner, and cell viability decreased significantly. However, cytotoxicity was reduced on treatment with unpreserved FML. Hematoxylin-eosin staining revealed surface desquamation, irregular surface, loss of cell borders, and stromal shrinkage in the group treated with BAC. On BAC exposure, tumor necrosis factor-α, interleukin-6, and human leukocyte antigen–DR were strongly detected, and cytotoxicity was markedly increased, as evidenced by a positive result in the terminal deoxynucleotidyl transferase dUTP nick end labeling assay. Ocular surface damage and inflammation were slightly reduced on treatment with preserved FML. In comparison, unpreserved FML did not induce morphological changes; moreover, decreased cell cytotoxicity and ocular surface inflammation were observed. Conclusions: The cytotoxicity of antiinflammatory eye drops evaluated in this study was induced by the preservative BAC. Accordingly, unpreserved FML is more effective than preserved eye drops in decreasing ocular inflammation.